PENGARUH MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN PADA AIR MINUM DALAM KEMASAN (AMDK) 3V - Agung Widhi Kurniawan; Muh. Ichwan Musa; Romansyah Sahabuddin; Zainal Ruma; Chessa Dessayanatasya Nursaid (MANAJEMEN DEWANTARA, 2023)
This study aims to determine the effect of Marketing Mix (Product, Price, Promotion, Place) on Purchasing Decisions at AMDK 3V KPRI UNM. The data used in this study are primary and secondary data with a total sample of 100 respondents. This study uses a quantitative approach and uses multiple linear regression analysis using SPSS 25 to prove the five hypotheses. The results showed that the t count of the product variable had a significant effect of 3.333 > t table of 1.985. The price variable is not valid but has a significant effect with a t-value of -4.003 < t-table of 1.985. The promotion variable has a significant effect with a t count of 3.371 > t table of 1.985. The place variable has a significant effect with a calculated t value of 3.284 > t table of 1.985. Based on the F test simultaneously on product, price, promotion, and place variables on purchasing decisions on 3V bottled water consumers with F count of 10.832 this shows F count (10.832) > F table (2.467) then Ho is rejected and Ha is accepted. The results of the study prove that the product, price, promotion and place variables together have an influence and are significant on the purchasing decision variable (dependent) on AMDK 3V.